PENGEMBANGAN PERANGKAT PEMBELAJARAN MODEL TEAMS GAME TOURNAMENT PADA MATERI MEMBACA PERMULAAN KELAS 1 SEKOLAH DASAR - Febriyanti Ryan Ariyani; Muhajir; Nuril Huda (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The aims of this research is to produce learning tools (RPP, LKPD, LP) with the Indonesian "Teams Game Tournament" (TGT) model on the introductory material to read and see the process of developing Indonesian language learning tools with the "Teams Game Tournament" (TGT), early reading model for first grade of primary school. This research uses research R&D or development research. The procedure used is the ADDIE development theory. ADDIE development theory consists of stages of Analysis, Design, Development, Implementation, Evaluation. However, the Implement and Evalute stages were not carried out because of the Covid-19 outbreak. The feasibility test of learning devices is carried out to obtain feasibility results through experts. The results showed that the "Teams Game Tournament" learning model was feasible to see from the results of expert validation which showed the proportion of the RPP validation value was 81%, LKPD 90% and LP 76.4%.